Meta Analysis The Effect of Challenge Based Learning on Mathematics Thinking Ability - Alfauzan Ridho Zulfikri; Ardhi Prabowo; Scolastika Mariani; Isnaini Rosyida (Universitas Teknokrat Indonesia, 2026)
This research aims to analyse the effect of implementing the Challenge Based Learning (CBL) model on students' mathematics thinking ability through a meta-analysis approach. Although mathematics plays an important role in developing students' mathematics thinking ability, international studies such as PISA show that mathematical skills in Indonesia are low. One strategy to improve these skills is through innovative learning models, one of which is CBL. CBL combines problem-based learning, project-based learning, and real-life contexts to solve relevant challenges. Based on a literature review, the application of CBL has been proven effective in improving mathematics thinking abilily such as creative thinking, critical thinking, mathematical reasoning, and numeracy literacy. Meta-analysis combines data from relevant studies by calculating the effect size to evaluate the impact. The results of the analysis show that the CBL model has a very high influence on students' mathematics thinking ability, with an average effect size of 4.028, which is classified as very high. The t-test also confirmed that there was a significant difference between the pretest and posttest scores (tcount = 35.05 > ttable = 19.97), confirming that CBL had an effect on improving mathematical thinking skills. Based on these findings, the CBL model is recommended as a learning model to improve mathematical thinking skills in mathematics education.